One‐Step Preparation of Viologen‐TiO2 Nanoparticles via a Hydrothermally Assisted Sol–Gel Process for Use in Electrochromic Films and Devices. (3rd September 2018) - Viñuales, Ana; Herbig, Bettina; Alesanco, Yolanda; Palenzuela, Jesús; Rodriguez, Javier; Schmitt, Angelika; Posset, Uwe
Abstract: A one‐step method based on a hydrothermally assisted sol–gel process for the preparation of electrochromic viologen‐modified TiO2 nanoparticles is presented. The simplicity of the proposed one‐step synthesis and its usefulness for the subsequent preparation of transparent electrochromic films is demonstrated. In this method, the viologen moieties are attached during the growing/crystallization process of the TiO2 nanoparticles; therefore, neither sintering nor immersion into viologen solution of the resulting nanostructured film as in the standard methods is required. Thus, this novel approach is compatible with plastic substrates and easier to scale‐up. The morphology of the films is characterized by means of X‐ray diffraction, scanning electron microscopy, and ellipsometric porosimetry experiment, while the presence of viologen moieties in and throughout the film is detected by means of diffuse reflectance infrared Fourier transform and X‐ray photoelectron spectroscopy. Finally, full cells are assembled both on conducting glass and polyester substrates to demonstrate that electrochromic devices with excellent performance (Δ T % = 58% and 48%, respectively) can be made with films deposited from viologen‐TiO2 nanoparticulate dispersions obtained by this method. Abstract : A novel method based on a hydrothermally assisted sol–gel process for the one‐step preparation of viologen‐modified TiO2 electrochromic nanoparticles is presented. The process consists in grafting the electrochromic viologen moieties during the crystallization of the TiO2 nanoparticles. The resulting nanoparticulate gels are redispersed and used for the deposition of films on conducting substrates and the subsequent assembly of electrochromic devices.